The role and possible mechanism of lncRNA Abib92159.2 in modulating adipocyte differentiation. (April 2019) - Yuan, Yingdi; Cao, Xinguo; Hu, Jiaojiao; Li, Jingyun; Shen, Dan; You, Lianghui; Cui, Xianwei; Wang, Xing; Zhou, Yahui; Gao, Yao; Zhu, Lijun; Xu, Pengfei; et al.
Abstract : Obesity is a major risk factor for metabolic diseases, while adipocyte differentiation is closely related to obesity occurrence. Long noncoding RNAs (lncRNAs) are a unique class of transcripts in regulation of various biological processes. Using lncRNA microarray, we found lncRNA Abib92159.2 was highly expressed in differentiated HPA-v and located ~247 bp upstream of the TMEM18, which was associated with BMI and obesity. We aimed to explore the role of Abib92159.2 in adipogenesis and the underlying mechanisms. The effects of Abib92159.2 gain- and loss-of-function on HPA-v adipogenesis were determined with lentivirus and siRNA-mediated cell transduction, respectively. Lipid accumulation was evaluated by oil red O staining; the expression of Abib92159.2, TMEM18 and several adipogenesis makers in HPA-v were analyzed by qPCR/Western blot. We found that the expression of Abib92159.2 gradually increased during HPA-v differentiation, and its expression in omental adipose tissue was positively related with BMI among 48 human subjects. Overexpression of Abib92159.2 promoted adipocytes differentiation while knockdown of it led to an adipogenic defect. Moreover, the expression of Abib92159.2 and TMEM18 were positively correlated during adipogenic differentiation. Abib92159.2 overexpression boosted TMEM18 expression while Abib92159.2 knockdown restrained TMEM18 expression. Further rescue experiments showed that TMEM18 knockdown partially restrained adipogenic differentiation in Abib92159.2 overexpressed HPA-v and adipogenic defect caused by Abib92159.2 knockdown could be rescued by TMEM18 overexpression. Luciferase reporter assays revealed that Abib92159.2 had a transcriptional activation effect on TMEM18. We concluded that lncRNA Abib92159.2 promoted human adipocytes differentiation possibly by regulating TMEM18.